2017
DOI: 10.1016/j.bjm.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing culture conditions for production of intra and extracellular inulinase and invertase from Aspergillus niger ATCC 20611 by response surface methodology (RSM)

Abstract: The aim of this study was obtain a model that maximizes growth and production of inulinase and invertase by Aspergillus niger ATCC 20611, employing response surface methodology (RSM). The RSM with a five-variable and three-level central composite design (CCD) was employed to optimize the medium composition. Results showed that the experimental data could be appropriately fitted into a second-order polynomial model with a coefficient of determination (R2) more than 0.90 for all responses. This model adequately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 25 publications
5
26
1
1
Order By: Relevance
“…This may be attributed to the elevation in medium's viscosity with increased fungal biomass, creating a nutritional imbalance in the medium and making the cells physiologically incapable to produce the enzyme. Our findings corroborate the results of inulinase production from Kluyveromyces marxianus (Singh et al 2007c) and A. niger (Dinarvand et al 2017). Appropriate agitation rate is a basic requirement for carrying out successful fungal aerobic fermentations.…”
Section: Effect Of Independent and Interacting Process Variables On Isupporting
confidence: 88%
See 1 more Smart Citation
“…This may be attributed to the elevation in medium's viscosity with increased fungal biomass, creating a nutritional imbalance in the medium and making the cells physiologically incapable to produce the enzyme. Our findings corroborate the results of inulinase production from Kluyveromyces marxianus (Singh et al 2007c) and A. niger (Dinarvand et al 2017). Appropriate agitation rate is a basic requirement for carrying out successful fungal aerobic fermentations.…”
Section: Effect Of Independent and Interacting Process Variables On Isupporting
confidence: 88%
“…The optimal temperature for growth and metabolite production for most of the fungal sources lies between 25-30 °C. In a number of studies, high inulinase production at low temperature from A. niger (Dinarvand et al 2017), A. tamarii (Saber and Noura 2009), P. subrubescens (Mansouri et al 2013) and Rhizopus oligosporus (Mohamed et al 2015) has also been reported. Incubation time and inoculum size are also very crucial factors for enzyme production.…”
Section: Effect Of Independent and Interacting Process Variables On Imentioning
confidence: 99%
“…The experimental statistic design was combined with response surface methodology (RSM), this method proving to be efficient in the development and optimization of the formulation of different pharmaceutical systems and technological processes [ 31 , 32 , 51 , 52 , 53 , 54 , 55 , 56 ] as it allows the researcher to investigate the simultaneous effects of formulation factors, to evaluate the interactions effects on system responses, to provide predictive mathematical models, and also to reduce the number of experiments saving in this way both time and resources [ 52 , 55 , 56 , 57 , 58 , 59 ]. The optimization technique was complemented with the Taguchi approach in order to set—through the Signal-to-Noise indicator (S/N ratio)—the adequate variation conditions for the formulation factors in order to ensure the products’ quality and process robustness [ 31 , 32 , 60 , 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction effects of variables on the calculated responses (intracellular and extracellular inulinase) were studied by plotting 3D surface curves against any two independent variables, as shown in Figs. 6 and 7 [17,6]. The specialized software package Signal processing toolbox for MATLAB 8.1 was used for processing the experimental data.…”
Section: Fig 3 Influence Of the Inoculum Concentration On Intracellmentioning
confidence: 99%